Computerized-Adaptive vs. Traditional Ratings of Depression and Suicidal Thoughts: An Assay Sensitivity Pilot Study in a Ketamine Clinical Trial - Grunebaum, Michael F.; Mann, J. John; Galfalvy, Hanga C.; Gibbons, Robert D. (Frontiers in Psychiatry, 2021)
There is a public health need for improved suicide risk assessment tools. This pilot methodology study compared the assay sensitivity of computerized adaptive tests (CAT) of depression and suicidal ideation versus traditional ratings in a randomized trial subgroup. The last 20 persons to enroll in a published ketamine trial in suicidal depression were studied. This subgroup received traditional and CAT ratings at baseline, 24 hours post-infusion and follow-up week 2, 4 and 6: Hamilton Depression Rating Scale, Beck Depression Inventory, and Beck Scale for Suicidal Ideation versus the CAT-Depression Inventory and CAT-Suicide Scale. Results showed larger effect sizes (ES) for CAT compared with traditional clinician-rated and self-report scales. Coefficients of variation for baseline measurements were lower for CAT compared with traditional scales. This is the first study to show that CAT may have greater assay sensitivity for treatment effects, particularly for suicidal ideation, compared with traditional clinician-rated and non-adaptive self-rated scales in a randomized trial. The findings suggest CAT can enable quick long-term follow-up assessments via cellphone, tablet, or computer while minimizing response bias due to repeated measurement of the same symptom items.